The Chinese Christology of T.C. Chao - Chen, Yongtao. (Theology and Mission in World Christianity, 2017)
This volume offers a careful analysis of the contextual Christology of T. C. Chao, one of the most important Chinese theologians and Chinese church leaders in the first half of twentieth century. At the core of Chao's Christology is the encounter between Christianity and the Chinese people, in particular the Chinese Christians. In response to the rapid social changes in China between 1910-1950, he attempted to develop a relevant theology by focusing on the characteristics of Christianity and, at the same time, aiming to understand Christianity within its Chinese context.